The aetiology of pneumonia from analysis of lung aspirate and pleural fluid samples: Findings from the PERCH study - Ebruke, B.E.; Knoll, Maria Deloria; Haddix, M.; Zaman, S.M.A.; Prosperi, C.; Feikin, D.R.; Hammitt, Laura L.; Levine, Orin S.; O’Brien, Katherine L.; Murdoch, D.R.; Brooks, W.A.; Scott, J.A.G.; et al. (Oxford University Press, 2021)
Background An improved understanding of childhood pneumonia aetiology is required to inform prevention and treatment strategies. Lung aspiration is the gold standard specimen for pneumonia diagnostics. We report findings from analyses of lung and pleural aspirates collected in the Pneumonia Etiology Research for Child Health (PERCH) study. Methods The PERCH study enrolled children aged 1–59 months hospitalized with World Health Organization defined severe or very severe pneumonia in 7 countries in Africa and Asia. Percutaneous trans-thoracic lung (LA) and pleural fluid (PF) aspiration was performed on a sample of pneumonia cases with radiological consolidation and/or pleural fluid in 4 countries. Venous blood and nasopharyngeal/oropharyngeal swabs were collected from all cases. Multiplex quantitative PCR and routine microbiologic culture were applied to clinical specimens. Results Of 44 LAs performed within 3 days of admission on 622 eligible cases, 13 (30%) had a pathogen identified by either culture (5/44) or by PCR (11/29). A pathogen was identified in 12/14 (86%) PF specimens tested by either culture (9/14) or PCR (9/11). Bacterial pathogens were identified more frequently than viruses. All but one of the cases with a virus identified were co-infected with bacterial pathogens. Streptococcus pneumoniae (9/44 [20%]) and Staphylococcus aureus (7/14 [50%]) were the predominant pathogen identified in LA and PF, respectively. Conclusions Bacterial pathogens predominated in this selected subgroup of PERCH participants drawn from those with radiological consolidation or pleural fluid, with S. pneumoniae and S. aureus the leading pathogens identified.